Housing Finance : World Bank Group Support for Housing Finance - Independent Evaluation Group (World Bank, Washington, DC, 2016)
Access to adequate housing is critically important to the health and wellbeing of the world’s population. Yet, despite the fact that this statement is part of the United Nations Universal Declaration of Human Rights and has been on the global policy agenda for many years, hundreds of millions of people continue to live in inadequate conditions with little or no access to decent housing. The demand for housing solutions will increase as urbanization and population growth persists. The United Nations Human Settlements Program (UN-Habitat) has estimated that the number of people living in slums around the world will rise to 900 million by 2020 if nothing is done. Asia and Africa will face special challenges, because urbanization in those regions is proceeding rapidly. Housing is frequently unaffordable to all but the top earners. A recent report estimates a housing affordability gap affecting 330 million households, with 200 million households in the developing world living in slums (McKinsey Global Institute 2014). Research has shown that more and better housing increases the welfare of occupants. Homeownership may increase stability and civic engagement, and provide financial security in old age. Improvements in housing also have important benefits to the economy. Housing construction and home improvement generate demand for professional, skilled, semi-skilled, and unskilled labor; and allow many micro and small businesses to flourish. The housing market is an important component of national economies and housing booms and busts can have significant effects on the macro economy and financial sector. The core purpose of this learning product is to generate knowledge and provide lessons learned from World Bank Group support to housing finance. Lessons were derived primarily from evaluated interventions in the form of World Bank loans or International Finance Corporation (IFC) investments and advisory services. World Bank technical assistance and knowledge products and interventions on housing finance matters were considered when provided in the context of lending operations. One limitation faced in preparation of this learning product was the lack of coverage of stand-alone World Bank advisory services.